Progressive Party in the Kingdom of Serbia from 1887 to 1896 - Pešić, Miroslav D (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The paper explores the history of the Serbian Progressive Party in the Kingdom of Serbia from 1887 to 1896. After the fall of the government of Milutin Garašanin in June 1887, the Serbian Progressive Party ended among the opposition parties. After the fall of the Progressive Party from power, the first coalition liberal-radical government was formed, headed by Jovan Ristić. The Progressive Party members and supporters were persecuted by the ruling People’s Radical Party. The Progressive Party lost the voters and deputies in the National Assembly, which suggested that it would not be able to recover for an extended period. However, less than two years later, in May 1889, the Progressive Party managed to organize a General Assembly, attended by over 2,000 members, who adopted the party program and statute which did not differ substantially from the one from 1881. It was quite obvious that the party leadership wanted to show that the Progressive Party did not disappear from the political scene, but that it temporarily withdrew to reconsolidate and focus on gathering voters. Yet, due to the unrest that erupted in Belgrade during the party assembly, the Party leadership announced in June 1889 that the Progressive Party would temporarily suspend its activities. As the withdrawal from the political scene did not produce any results, the Party leaders decided to resume the Party’s activities, hoping that the situation would eventually change in their favor. In the September 1890 elections, the Progressive Party won one parliamentary mandate, which went to the Party’s leader, Milutin Garašanin. In the National Assembly, his political struggle against the ruling Radical Party government was hardly observable, but his articles published in the Progressive Party newpaper ‘Videlo’ (Daylight) had a much greater impact on the readers. During the minority liberal government of Jovan Avakumović, in 1892-1893, there were attempts to reach an agreement on a pre-election coalition between the Liberals and the Progressives against the Radicals, but these attempts failed. After the coup of 1st April 1893, when the Radicals regained power, it was quite clear to the Progressive Party leaders that they could not fight the Radicals on their own. The idea of forming a new political grouping of liberals and progressives was soon abandoned. After the 1888 Constitution had been repealed and the 1869 Constitution had been reinstated, King Alexander tried (with the assistance of rare non-partisan people) to avoid the intransigence of the Progressive Party leaders and the supremacy of the Radicals. After the period of several neutral governments headed by Đorđe Simić (January - April 1894), Svetomir Nikolajević (April - October 1894), and Nikola Hristić (October 1894 - July 1895), the Progressive Party government headed by Stojan Novaković (July 1895 - December 1896) was formed. This government initiated a change in the Constitution but the idea was not upheld by King Alexander, as the Liberals and the Radicals did not agree to instituting the constitutional reform under the administration of the weakest party in the country. In such circumstances, Novaković resigned on 29 December 1896. The next day, the Progressive Party was dissolved by the decision of the Party leadership.